Порушення показників протеїназо-інгібіторної системи в легенях морських свинок у пізній період формування експериментальної бронхіальної астми = The features of state changes of proteinase-inhibitory system in the lungs of guinea pigs in the later period of experimental bronchial asthma - Regeda, M. S.; Kolishetska, M. A.; Kachmarska, M. O.; Zastryzhna, M. L. (Journal of Education, Health and Sport, 2016)
Reheda M. S., Kolishetska M. A., Kachmarska M. O., Zastryzhna M. L. Порушення показників протеїназо-інгібіторної системи в легенях морських свинок у пізній період формування експериментальної бронхіальної астми = The features of state changes of proteinase-inhibitory system in the lungs of guinea pigs in the later period of experimental bronchial asthma. Journal of Education, Health and Sport. 2016;6(1):189-196. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45336 http://ojs.ukw.edu.pl/index.php/johs/article/view/45336 https://pbn.nauka.gov.pl/works/709850 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. УДК: 616.24:616.248-039.36-092.9]:577.15.024/.025 Порушення показників протеїназо-інгібіторної системи в легенях морських свинок у пізній період формування експериментальної бронхіальної астми The features of state changes of proteinase-inhibitory system in the lungs of guinea pigs in the later period of experimental bronchial asthma М. С. Регеда, М. А. Колішецька , М. О. Качмарська, М. Л. Застрижна M. S. Reheda, M. A. Kolishetska, M. O. Kachmarska, M. L. Zastryzhna Львівський національний медичний університет ім. Данила Галицького Danylo Halytskiy Lviv National Medical University Abstract Analysis of the research shows that in all groups the increased intensity of lysis proteins was found. These changes probably occurred as a result of a significant imbalance in the system of tissue proteinase inhibitors. In particular, we have found, that there is an increase of azoalbumin by 49,43% (p ≤0,05) against of control group, in the later period on the 26th day of experimental bronchial asthma (BA). On the 33rd day, the level of lysis experienced even greater growth by 85,9% (p ≤0,05) in comparison with the animal intact group, which indicates about the intense stimulation of proteolytic activity in the lungs. Determination of azokasein in the lungs in this experimental model showed a progressive increase of its contents in the lungs on the 26th and 33rd days by 64,6% (p ≤0,05) and 96,3% (p ≤0,05) against of control sizes, that confirms the activation processes of proteolysis. The research of azokolagen has the important value for characteristic of the activity of protein lysis. We have found its gradual increase in the lung, depending on the duration of the antigenic factor. So, on the 26th and the 33rd day of experimental (BA) the increase of content of azokolagen by 70,8% (p ≤0,05) and 79,2% (p ≤0,05) was observed by comparing with the first group of guinea pigs. The content of protein inhibitors in animals with experimental BA has also undergone significant changes in the later period. There was found the authentic reduction of α2-macroglobulin, accordingly, by 30,7% (p ≤0,05) and by 48,5% (p ≤0,05) comparatively to control. As for the research of α1-protease inhibitor in the lungs in the dynamics of the development of the experimental asthma we observe its decrease by 27,7% (p ≤0,05) on the 26th day in comparison with the first group of the animals. Subsequently on the 33rd day of the experiment the decrease of the investigated marker reached 36,1% (p ≤0,05) against intact animals. Evaluating the results of conducted biochemical researches of indicators of proteinase inhibitory system, we can make a conclusion about significant advantage of process of protein catabolism, which increases with the development of pathological process and is a powerful damaging factor and at the same time reducing protection. So, there was found gradual intensive growth of azoalbumin, azokaseein and azokolagen in the lungs in the later period of the formation of asthma, that is especially expressed on the 33rd day of the experiment. The dynamics of the proteinase inhibitor activity is characterized by the decrease of all investigated markers, both on the 26th and on the 33rd day of experimental asthma, that indicates about their oppression. The obtained results give reason to think about the imbalance in the proteinase-inhibitory system with advantage of proteyinase potential on the background of the depression of inhibitors, especially in the later period. Key words: asthma, proteinase-inhibitory system. Резюме Аналіз результатів дослідження свідчить про те, що в усіх групах було встановлено підвищення інтенсивності лізису протеїнів. Зазначені зміни, ймовірно, виникли внаслідок істотного дисбалансу у системі тканинних інгібіторів протеїназ. Зокрема, нами було встановлено, що в пізній період на 26-у добу експериментальної моделі бронхіальної астми (БА) відбувається підвищення азоальбуміну на 49,43% (р ≤0,05) проти групи контролю. На 33-ю добу рівень його лізису зазнавав ще більшого зростання на 85,9% (р ≤0,05) в порівнянні з тваринами інтактної групи, що свідчить про інтенсивну стимуляцію протеолітичної активності в легенях. Визначення азоказеїну в легенях при даній експериментальній моделі показало поступове підвищення його вмісту в легенях на 26-у і 33-ю доби відповідно на 64,6% (р ≤0,05) і 96,3% (р ≤0,05) проти контрольних величин, що підтверджує активізацію процесів протеолізу. Важливе значення для характеристики активності лізису білків має дослідження також азоколагену. Нами виявлено його поступове зростання в легенях в залежності від тривалості дії антигенного фактора. Так, на 26-у і 33-ю доби експериментальної БА спостерігалося зростання вмісту азоколагену відповідно на 70,8% (р ≤0,05) і 79,2% (р ≤0,05) при порівнянні з першою групою морських свинок. Вміст білкових інгібіторів у тварин з експериментальною БА також зазнавав виражених змін у пізньому періоді. Встановлено достовірне зниження рівня α2-макроглобуліну відповідно на 30,7% (р ≤0,05) та на 48,5% (р ≤0,05) відносно контролю. Щодо дослідження α1-інгібітора протеаз в легенях у динаміці розвитку експериментальної бронхіальної астми, то спостерігаємо його зниження на 27,7% (р ≤0,05) на 26-у добу в порівнянні з І групою тварин. В подальшому на 33-ю добу експерименту спад досліджуваного нами маркера досягнув 36,1% (р ≤0,05) проти інтактних тварин. Оцінюючи результати проведених біохімічних досліджень показників протеїназо-інгібіторної системи, можна зробити висновок про суттєву перевагу процесів катаболізму протеїнів, яка зростає по мірі розвитку патологічного процесу і є потужним пошкоджувальним фактором, і, водночас, зниження системи захисту. Так, встановлено поступове інтенсивне зростання азоальбуміну, азоказеїну та азоколагену в легенях у пізній період формування бронхіальної астми, особливо виражене на 33-ю добу експерименту. Динаміка активності інгібіторів протеїназ характеризується зниженням всіх досліджуваних маркерів, як на 26-у, так і на 33-ю доби експериментальної БА, що свідчить про їх пригнічення. Одержані результати дають підставу думати про порушення балансу в системі у протеїназо-інгібіторній системі з перевагою протеїназного потенціалу на тлі депресії інгібіторів, особливо у пізній період. Ключові слова: бронхіальна астма, протеїназо-інгібіторна система. Резюме Нарушения показателей протеиназно-ингибиторной системы в легких морских свинок в поздний период формирования экспериментальной бронхиальной астмы. Анализ результатов исследования свидетельствует о том, что во всех группах было установлено повышение интенсивности лизиса протеинов. Отмеченные изменения, вероятно, возникли в результате существенного дисбаланса в системе тканевых ингибиторов протеиназ. В частности, нами было установлено, что в поздний период на 26-ые сутки экспериментальной модели бронхиальной астмы (БА) происходит повышение азоальбумина на 49,43% (р ≤0,05) против группы контроля. На 33-ю сутки уровень его лизиса испытывал еще больший рост на 85,9% (р ≤0,05) по сравнению с животными интактной группы, которая свидетельствует об интенсивной стимуляции протеолитической активности в легких. Определение азоказеина в легких при данной экспериментальной модели показало постепенное повышение его содержимого в легких на 26-ые и 33-ие сутки соответственно на 64,6% (р ≤0,05) и 96,3% (р ≤0,05) против контрольных величин, что подтверждает активизацию процессов протеолиза. Важное значение для характеристики активности лизиса белков имеет исследование также азоколлагена. Нами выявлен его постепенный рост в легких в зависимости от длительности действия антигенного фактора. На 26-ые и 33-ие сутки экспериментальной БА наблюдался рост содержимого азоколлагена соответственно на 70,8% (р ≤0,05) и 79,2% (р ≤0,05) при сравнении с первой группой морских свинок. Содержимое белковых ингибиторов у животных с экспериментальной БА также испытывал выраженные изменения в позднем периоде. Установлено достоверное снижение уровня α2-макроглобулина соответственно на 30,7% (р ≤0,05) и на 48,5% (р ≤0,05) относительно контроля. Относительно исследования α1-ингибитора протеаз в легких в динамике развития экспериментальной бронхиальной астмы, то наблюдаем его снижение на 27,7% (р ≤0,05) на 26-ые сутки по сравнению с І группой животных. В дальнейшем на 33-ие сутки эксперимента спад исследуемого нами маркера достиг 36,1% (р ≤0,05) против интактных животных. Оценивая результаты проведенных биохимических исследований показателей протеиназо-ингибиторной системы, можно сделать вывод о существенном преимуществе процессов катаболизма протеинов, которая растет по мере развития патологического процесса и является мощным разрушительным фактором, и, в то же время, снижение системы защиты. Так, установлен постепенный интенсивный рост азоальбумина, азоказеина и азоколлагена в легких в поздний период формирования бронхиальной астмы, особенно выраженное на 33-ие сутки эксперимента. Динамика активности ингибиторов протеиназ характеризуется снижением всех исследуемых маркеров, как на 26-ые, так и на 33-ие сутки экспериментальной БА, что свидетельствует об их притеснении. Полученные результаты дают основание думать о нарушении баланса в системе в протеиназо-ингибиторной системе с преимуществом протеиназного потенциала на фоне депрессии ингибиторов, особенно в поздний период. Ключевые слова: бронхиальная астма, протеиназо-ингибиторная система.